Proteomic and metabolic profiles of Cakile maritima Scop. Sea Rocket grown in the presence of cadmium. Issue 4 (2nd February 2015) - Taamalli, Manel; D'Alessandro, Angelo; Marrocco, Cristina; Gevi, Federica; Timperio, Anna Maria; Zolla, Lello
Abstract : Recent physiological reports have documented how Cakile maritima Scop. Sea Rocket could accumulate high doses of Cd without altering its physiological parameters. Abstract : Recent physiological reports have documented how Cakile maritima Scop. Sea Rocket could accumulate high doses of Cd without altering its physiological parameters. In the present study, we performed an integrated proteomics (2DE) and metabolomics (HPLC-MS) investigation to determine the molecular mechanisms underlying cadmium (Cd) tolerance of this halophyte. Peculiar features were observed: (i) up-regulation of thiol compound anabolism, including glutathione and phytochelatin homeostasis, which allows an intracellular chelation of Cd and its compartmentalization into vacuole by a significant up-regulation of vacuolar transporters; (ii) up-regulation of the PPP and Calvin cycle (both at the enzyme and metabolite level), which utterly promoted the maintenance of NADPH/NADP + homeostasis, other than the accumulation of triose-phosphates (serving as anabolic intermediates for triacylglycerol biosynthesis) and the glyoxylate precursor phosphoglycolate, to promote photorespiration and consequently CO2 release. An up-regulation of carbonic anhydrase was also observed. This halophyte is also correlated with a highly efficient antioxidant system, especially a high up-regulation of SOD1, resulting more efficient in coping with heavy metals stress than common plants. Interestingly, exposure to high Cd concentrations partly affected photosystem integrity and metabolic activity, through the up-regulation of enzymes from the Calvin cycle and glutathione–ascorbate homeostasis and PAP3 which stabilizes thylakoid membrane structures. In addition, up-regulation of Peptidyl-prolyl isomerase CYP38 increases stability and biogenesis of PSII. Finally, metabolomics results confirmed proteomics and previous physiological evidence, also suggesting that osmoprotectants, betaine and proline, together with plant hormones, methyl jasmonate and salicylic acid, might be involved in mediating responses to Cd-induced stress. Taken together, these peculiar features confirm that Cakile maritima Scop. Sea Rocket seemed to be naturally equipped to withstand even high doses of Cd pollution.